The mouthfeel of black tea beverages - Hofmann, Saskia Iris (2018)
The mouthfeel and texture of food and beverage products play an important role in consumer liking. However, to date these key sensory properties have received limited attention from researchers and our understanding of texture and mouthfeel perception in food remains restricted. For tea, a popular beverage enjoyed around the globe, astringency is the most frequently highlighted mouthfeel attribute. Since black tea is commonly consumed with milk and sugar, research investigating the mouthfeel of tea as impact by these added ingredients is of commercial interest. The aim of this PhD research was to gain a better understanding of the mouthfeel perception of black tea beverages using sensory and instrumental methods. In order to achieve this, a model system consisting of black tea instant powder, sugar, and fat (added as oil-in-water emulsion) was developed which allowed for the independent variation of the design factors (tea, sugar, fat). Firstly, a mouthfeel lexicon was developed using Quantitative Descriptive Analysis (QDA), and the impact of tea, sugar and fat on the perception of selected attributes was assessed by a trained panel (n=10) using a Design of Experiments approach to generate predictive polynomial models from a D-optimal design. Furthermore, the temporal perception of astringency and bitterness over multiple sips of tea was assessed by a trained panel(n=9) using Time Intensity measures. The effect of sweetness and viscosity from sucrose was decoupled using sweeteners and thickeners and the effect of sugar on astringency and bitterness perception was investigated in more detail. Once the mouthfeel perception of black tea beverages was explored, instrumental methods were deployed to reveal possible correlations between instrumental parameters and mouthfeel perception. Two instrumental methods were used: a force plate to measure the frictional and vibrational behaviour of tea samples, whilst an accelerometer was used to measure vibrations related to tongue movements using a technique called “acoustic tribology”. The results showed that besides astringency, fat-driven attributes, such as “thickness”, “slipperiness” and “mouth coating”, play a significant role in the mouthfeel perception of black tea beverages. Predictive polynomial models revealed the complex effects of key ingredients on the mouthfeel of tea. The results showed that tea was not a significant factor (p>0.05) for the attributes “thickness” and “mouth coating”, whereas for all other attributes all three design factors affected perception significantly (p<0.001). It was found that astringent and bitter intensity was reduced by the addition of fat and sugar in a similar fashion. However, when evaluated over time, it was found that astringency and bitterness had distinctly different temporal profiles in tea, illustrating the importance of temporal ratings. A build-up in astringency and bitterness intensity with increasing number of sips gave further insight into the perception of both attributes during tea consumption, representing a normal tea drinking behaviour. Furthermore, the data indicated that sugar reduces astringency due to its sweetness and not the rise in viscosity. The results from the force plate experiment showed that the addition of 5% fat significantly reduced the friction coefficient of tea samples (p<0.0001) and that an addition of 10% fat did not reduce the friction coefficient further (p=0.97). It was also shown that the friction coefficient did not vary significantly between tea levels (p=0.324). The results also revealed that fat-driven attributes were negatively correlated to friction and that astringency was a complex precept, which was difficult to predict using instrumental methods, resulting in a poor correlation between friction coefficient and astringency (R2=0.16). The results from the “acoustic tribology” experiment indicated that mouthfeel was linked to measured vibrations caused by tongue movements. Furthermore, differences in tea composition resulted in different oral vibrations, and it was observed that for example “thick” is positively correlated to low frequency vibrations. The results of this research on the perceived mouthfeel of tea provide much needed insight into this key sensory property of tea. These results will be further useful for product developers interested in producing ready-todrink tea beverages where mouthfeel is likely to be a critical factor for consumer liking and commercial success.